Hydrological and sedimentary analyses of well‐preserved paleofluvial‐paleolacustrine systems at Moa Valles, Mars. Issue 2 (23rd February 2016) - Salese, Francesco; Di Achille, Gaetano; Neesemann, Adrian; Ori, Gian Gabriele; Hauber, Ernst
Abstract: Moa Valles is a well‐preserved, likely Amazonian (younger than 2 Ga old), paleodrainage system that is nearly 300 km long and carved into ancient highland terrains west of Idaeus Fossae. The fluvial system apparently originated from fluidized ejecta blankets, and it consists of a series of dam breach paleolakes with associated fan‐shaped sedimentary deposits. The paleolakes are interconnected and drain eastward into Liberta crater, forming a complex and multilobate deltaic deposit exhibiting a well‐developed channelized distributary pattern with evidence of switching on the delta plain. A breach area, consisting of three spillover channels, is present in the eastern part of the crater rim. These channels connect the Liberta crater to the eastward portion of the valley system, continuing toward Moa Valles with a complex pattern of anabranching channels that is more than 180 km long. Based on hydrological calculations of infilling and spillover discharges of the Liberta crater lake, the formation of the whole fluvial system is compatible with short to medium (<1000 year) timescales, although the length and morphology of the observed fluvial‐lacustrine features suggest long‐term periods of activity based on terrestrial analogs. Water for the 300 km long fluvial system may have been primarily sourced by the melting of shallow ice due to the thermal anomaly produced by impact craters. The occurrence of relatively recent (likely Amazonian) hydrological activity, which could have been primarily supported by groundwater replenishment, supports the hypothesis that hydrological activity could have been possible after the Noachian‐Hesperian boundary, which is commonly considered as the onset epoch of the present cold‐dry climate. Key Points: Very well preserved anabranching paleofluvial systems Formation of the whole fluvial system is compatible with short‐medium (<1000 year) timescales Our results indicate the occurrence of relatively recent (Early Amazonian) hydrological activity